Increased risk of epilepsy in patients registered in the Swedish Dementia Registry. (13th August 2019) - Zelano, J.; Brigo, F.; Garcia‐Patek, S.
Abstract : Background and purpose: Data on epilepsy in dementia, particularly on its risk factors, are scarce. Confounding comorbidities and the rising incidence of epilepsy in older age have hampered studies in this field. The occurrence and risk factors for epilepsy in the Swedish Dementia Registry (SveDem), a large cohort of patients with dementia, have been examined. Methods: Information on epilepsy and seizure‐related diagnoses, comorbidities and survival were extracted for all individuals in SveDem ( n = 81 192) and three randomly selected age‐ and gender‐matched controls from the population register, excluding all with a dementia diagnosis ( n = 223 933). The risk of epilepsy following dementia diagnosis was estimated with Kaplan–Meier curves, and Cox proportional hazard modelling was used to identify risk factors and adjust for comorbidities. Results: A diagnosis of epilepsy was found more frequently amongst dementia patients [4.0%, 95% confidence interval (CI) 3.8–4.1] than controls (1.9%, 95% CI 1.9–2.0). The risk of incident epilepsy after dementia was 2.1% (95% CI 1.9–2.3) at 5 years and 4.0% (95%CI 3.4–4.6) at 10 years, compared to 0.8% (95% CI 0.8–0.8) and 1.6% (95% CI 1.4–1.8) respectively for controls. The risk was greatest for early‐onset Alzheimer's disease. In multivariate analysis, dementia was associated with a hazard ratio of 2.52 (95% CI 2.31–2.74) for epilepsy. Young age, male sex, stroke, brain trauma, brain tumour and low Mini‐Mental State Examination score significantly increased the risk. Conclusions: Dementia, particularly young‐onset Alzheimer's disease, increases the risk of subsequent epilepsy. Further studies are needed to determine optimal management and the impact of epilepsy on prognosis.